Navigating across anthropological and Haudenosaunee knowledge: Co-developing research using CBPR and Kaswenta (Two-Row Wampum) principles in partnership with Six Nations of the Grand River - Sultana, Afroza; Martin-Hill, Dawn; Wilson, Julie (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
As part of the Ohneganos research project, funded through the Global Water Futures (GWF), we document the ways we worked across Haudenosaunee and anthropological knowledge to assess the impact of water insecurity on holistic maternal health. This research was led by the Six Nation Birthing Center (SNBC), inspired by Haudenosaunee Kaswenta treaty principles. We utilized community-based participatory research (CBPR) and Indigenous research methods (IRMs), such as storytelling, to find common ground of dialogue and reciprocity. In doing so, this research goes beyond traditional anthropological ways of data collection and fieldwork and highlights the importance of active community direction and participation. We argue that different knowledge from the researchers does not need to be ignored or reduced to one singular perspective to work across worldviews. Instead, acknowledging and highlighting the differences will lead to innovative methods and scholarship. This paper contributes to the literature of research methods and policies and will be helpful to Indigenous communities and non-Indigenous researchers working together.